Do natural disasters change savings and employment choices? Evidence from Bangladesh and Pakistan - Shaikh M. S. U. Eskander; Samuel Fankhauser; Shikha Jha (Asian Development Bank (ADB), 2016)
We investigate the economic response of households to natural disasters in Bangladesh and Pakistan. In particular, we explore to what extent households adjust their income and employment strategies and savings in response to exposure to floods and storms. Using two unique panel datasets, we find evidence of autonomous adjustments in both countries. In Bangladesh, farmers move away from farm to nonfarm employment as a coping strategy to tackle immediate reductions in their total household income from exposure to disasters, whereas nonfarmers increase their off-farm labor supply. Such adjustments in employment strategies are stronger among the storm-affected households than the flood-affected households. On the other hand, although farmers in Pakistan move away from agriculture as an immediate response to disasters, they eventually come back to agriculture within a year of disaster exposure. We also identify that such adjustments in employment and income strategies help farmers to overcome the immediate losses from disaster exposure as the disasteraffected households from both Bangladesh and Pakistan exhibit at least no decrease in their savings behavior. We discuss policy implications in terms of developing nonfarm employment opportunities to reduce the future harms of disaster and financing economic migration to reduce income vulnerability.
Keywords: D13; D64; Q15; Q24; Q54; 330; Bangladesh; income; natural disasters; Pakistan; savings